2023
DOI: 10.1002/14651858.cd007784.pub3
|View full text |Cite
|
Sign up to set email alerts
|

HMG CoA reductase inhibitors (statins) for people with chronic kidney disease not requiring dialysis

David J Tunnicliffe,
Suetonia C Palmer,
Brydee A Cashmore
et al.

Abstract: BACKGROUND: Cardiovascular disease (CVD) is the most frequent cause of death in people with early stages of chronic kidney disease (CKD), for whom the absolute risk of cardiovascular events is similar to people who have existing coronary artery disease. This is an update of a review published in 2009, and includes evidence from 27 new studies (25,068 participants) in addition to the 26 studies (20,324 participants) assessed previously; and excludes three previously included studies (107 participants). This upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 334 publications
0
2
0
Order By: Relevance
“…Furthermore, a phase 4 RCT to assess the potential benefits of acute pretreatment with a high dose of atorvastatin in contrast induced nephropathy patients with diabetes indicated for elective coronary intervention has been completed by 2020 (NCT04375787), and the data from this study are not publicly available. However, a cochrane database systematic review reported that there was insufficient data to definitively assess the potential benefits and harms of statin therapy in reducing the risk of death, major cardiovascular events, and myocardial infarction among individuals with CKD not requiring dialysis who did not have cardiovascular diseases at the initial evaluation [301].…”
Section: Other Novel Antioxidative Therapiesmentioning
confidence: 99%
“…Furthermore, a phase 4 RCT to assess the potential benefits of acute pretreatment with a high dose of atorvastatin in contrast induced nephropathy patients with diabetes indicated for elective coronary intervention has been completed by 2020 (NCT04375787), and the data from this study are not publicly available. However, a cochrane database systematic review reported that there was insufficient data to definitively assess the potential benefits and harms of statin therapy in reducing the risk of death, major cardiovascular events, and myocardial infarction among individuals with CKD not requiring dialysis who did not have cardiovascular diseases at the initial evaluation [301].…”
Section: Other Novel Antioxidative Therapiesmentioning
confidence: 99%
“…Review updates can have the same author composition as the previous version, although there are deviations (for example, see (19)(20)(21)(22)(23) and their previous versions). Also, in this study, the unit of analysis is a published paper and not a project.…”
Section: Data Sources and Retrievalmentioning
confidence: 99%